Navigating the Leadership Challenge Inside Indian Public Relations. (November 2015) - Patwardhan, Padmini
This study examines public relations (PR) leadership in India, offering empirical insights on perceptions of leadership among Indian practitioners, important PR leadership dimensions, salience of leadership abilities and development of future PR leaders in India. To provide breadth and depth to the investigation, data was collected through an industry survey and interviews with PR leaders. Results suggest that Indian practitioners recognize global principles and practices of effective PR leadership but also embrace Indian values. Specific leadership roles such as nurturer, seer and mentor along with practices such as 'the personal touch' were highlighted. Leaders stressed importance of ethics, an 'ideal' quality of excellence embedded in Indian leadership theory's simple living-high thinking concept. Personal influence is seen as part of leadership practice creating strong personal rather than contractual relationships. Collaboration rather than competition in leadership style reveals focus on collectivistic problem solving accomplished through teamwork and use of networks. Human resource issues and training are identified as dominant issues for PR in India and there are limited formalized structures for entry level or leadership training in the Indian PR industry. Leadership education is currently managed through personal mentoring by current leaders who adopt 'nurturer' roles central to Indian models of leadership management.